2016
DOI: 10.1016/j.stemcr.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Aberrations Are Not Specific to Transcription Factor-Mediated Reprogramming

Abstract: SummarySomatic cells can be reprogrammed to pluripotency using different methods. In comparison with pluripotent cells obtained through somatic nuclear transfer, induced pluripotent stem cells (iPSCs) exhibit a higher number of epigenetic errors. Furthermore, most of these abnormalities have been described to be intrinsic to the iPSC technology. Here, we investigate whether the aberrant epigenetic patterns detected in iPSCs are specific to transcription factor-mediated reprogramming. We used germline stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Similarly, imprinting errors are observed in iPSCs, suggesting that these epigenetic anomalies are related to the reprogramming process and could be directly responsible for the variable phenotypes and low success rates of both cloning and iPS derivation procedures [ 139 ]. Certainly, the epigenetic abnormalities detected in iPSCs are not specific to transcription factor-mediated reprogramming [ 140 ]. It is difficult to program via SCNT and iPSC induction, and it is also a challenge to cause two sperm from paternal genomes to construct a DSC embryo with the correct reprogramming procedure.…”
Section: Challenges Of Dsc Scnt and Ipscsmentioning
confidence: 99%
“…Similarly, imprinting errors are observed in iPSCs, suggesting that these epigenetic anomalies are related to the reprogramming process and could be directly responsible for the variable phenotypes and low success rates of both cloning and iPS derivation procedures [ 139 ]. Certainly, the epigenetic abnormalities detected in iPSCs are not specific to transcription factor-mediated reprogramming [ 140 ]. It is difficult to program via SCNT and iPSC induction, and it is also a challenge to cause two sperm from paternal genomes to construct a DSC embryo with the correct reprogramming procedure.…”
Section: Challenges Of Dsc Scnt and Ipscsmentioning
confidence: 99%
“…This concept stems from a number of works that investigated the differences in differentiation capacity of hiPSC and described them to epigenetic marks inherited from the cells of origin and that had not been correctly reset during the reprogramming process (Bar-Nur et al 2011, Ohi et al 2011). However, current knowledge suggests that the reprogramming process itself is prone to inducing epigenetic abnormalities (Tiemann et al 2016) and that the main factor influencing the differentiation propensity is not an epigenetic memory as such, but the (epi)-genetic background of the donor of the source cells (reviewed in Keller et al 2018).…”
Section: Suboptimal Differentiationmentioning
confidence: 99%
“…However, a comparison between lentiviral encoded transcription factor‐mediated reprogramming of germline stem cells (GSC) to iPSCs, to culture condition‐mediated reprogramming of the same GSC lines, demonstrated that the two methods were similar in both the retention of epigenetic marks characteristic of GSC and the incidence of epigenetic errors attributable to the reprogramming process. Thus, alternative reprogramming methods may not be superior to standard lentivirus‐based reprogramming in terms of epigenetic memory and induction of epigenetic errors .…”
Section: Induced Pluripotent Cellsmentioning
confidence: 99%